Investigation of dual anti-HIV/HSV activity of oxoquinoline-acylhydrazone derivatives by molecular docking - Yuri Inácio Marques Silva; Julliane Yoneda (Universidade de São Paulo, 2023)
Abstract Someoxoquinoline-acylhydrazonederivativesshowedactivityagainst HumanImmunodeficiency Virus type 1 (HIV-1). These compounds must also be active against Herpes Simplex Virus type 1 (HSV-1) by an inhibition mechanism where they interact with the HSV-DNA-polymerase/DNA-duplex complex. There are several treatment options for HSV-1 but there is no cure for the disease, which may represent a life risk for individuals co-infected with HIV. In this work molecular docking studies were carried out in an attempt to understand the dual activity of these oxoquinoline-acyhydrazone derivatives. The compounds were docked in two possible situations: (i) in the polymerase domain of HIV-1 Reverse Transcriptase (RT) enzyme in order to verify whether the inhibition occurs similarly to the proposed mechanism for HSV-1 inhibition, where the ligand would form a complex with the enzyme and the DNA; (ii) in the allosteric site of RT in order to verify if the inhibition occur in a similar way to non-nucleoside RT inhibitors (NNRTI). The studied compounds showed higher binding affinity to the allosteric site of RT and the results indicate that the inhibition should occur in a mechanism similar to that of NNRTI, which produces an allosteric inhibition that induces structural changes in the enzymatic active site.